Behaviour Study of Four Insecticides using different Mathematical Modeling - Jaafar A. Issa; Alaa H. Al-Farttoosy; Abdulnabi A. Matrood (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2023)
The adsorption, distribution coefficient, Langmuir and Freundlich models and the mathematical evaluation of pesticides have become more interesting from an environmental point of view. The outcomes revealed that indoxacarb, imidacloprid, and lambda-cyhalothrin are subjected to the Pseudo-first order reaction (PFO). The rate of degradation was reached, into 0.01, 0.07, and 0.04 a minute respectively. While chlorantraniliprole reached 0.00002 a minute. This indicates that these insecticides are decreasing in their concentrations depending only on the time. Hence, the time required to decrease 50% of each insecticide (DT50) was various periods. The DT50 for indoxacarb, imidacloprid, and lambda-cyhalothrin, and chlorantraniliprole 3.2, 1.9, 10.1, and 2.3 days respectively. The distribution Coefficient Kd as well scored (5.25, 1.30, 0.562, and 0.639) mL g-1 respectively. This indicated that indoxacarb, imidacloprid has a mobility behaviour, while the lambda-cyhalothrin and chlorantraniliprole are less mobile in the soil. In terms of Freundlich model (aF), chlorantraniliprole 2.82 and lambda-cyhalothrin 2.75 are more fit than indoxacarb 0.013 L g-1 and imidacloprid 0.249 L g-1 subjected to the Langmuir model (KL).